Serum Receptor Activator of Nuclear Factor-κβ Ligand and Osteoprotegerin Levels and Ratio in Correlation with Bone Mineral Density - Fauqa Arinil Aulia; Sri Lestari Utami; Leonita Anniwati; Sony Wibisono Mudjanarko; Ferdy Royland Marpaung (Indonesian Association of Clinical Pathologist and Medical laboratory, 2020)
Osteoporosis is a disorder represented by manifestations of low bone mass, decreased bone tissue, and disrupted bonemicroarchitecture. The diagnosis of osteoporosis so far has been based on fracture manifestations after minimal trauma orby detecting low Bone Mineral Density (BMD). Measurement of Receptor Activator of Nuclear Factor-κβ Ligand (RANKL)and Osteoprotegerin (OPG) levels has opened the discourse of a more specific assessment of osteoblast and osteoclastregulation. The RANKL/OPG ratio can represent resorption and bone formation more significantly when correlated withBMD features. This study aimed to analyze the correlation between serum RANKL and OPG levels and ratio with BMD. A totalof 58 post-menopausal females from 13 elderly in Integrated Community Health Care Surabaya and Sidoarjo were enrolled.Data were collected by recording age, onset of menarche, onset of menopause, and Body Mass Index (BMI). Serum RANKLand OPG levels were evaluated using sandwich ELISA from Elabscience®. The RANKL/OPG ratio was obtained from the ratiobetween measured RANKL and OPG levels in serum. The proximal femur and lumbar spine BMDs were measured usingHologic® Discovery™ QDR™ Dual-Energy X-ray Absorptiometry (DEXA). Pearson's correlation test in this study showed nosignificant correlation between BMD and RANKL levels (lumbar: p=0.203; hip: p=0.283). The insignificant result was alsoshown in the correlation between BMD and OPG levels (lumbar: p=0.412; hip: p=0.617). A significant result between lumbarBMD and RANKL/OPG ratio was only found in the osteopenia subjects (p=0.001). The RANKL/OPG ratio had a significantcorrelation only with osteopenia-BMD in post-menopausal females. Therefore, it could be used as supporting data inosteoporosis screening.